Retinopathy of Prematurity: A Brief Review of Literature - Hashemieh, Mozhgan; Nassiri, Nader (Journal of Ophthalmic and Optometric Sciences, 2017)
Abstract Retinopathy of prematurity is a vaso-proliferative retinal disorder occurring in preterm infants. With the increase in the survival of preterm infants, retinopathy of prematurity has become a major cause of childhood blindness worldwide. In this brief review the main aspects of this disease including pathogenesis, classification, epidemiology, screening and treatment are discussed. Keywords: Retinopathy of prematurity; Preterm, Incidence, Treatment, Classification, Screening.